A contextual information retrieval framework - Limbu, D; Connor, AM; MacDonell, SG (National Advisory Committee on Computing Qualifications (NACCQ), 2005)
The amount of information on the Internet is constantly growing and the challenge now is one of finding relevant information. Contextual information retrieval (CIR) is a critical technology for today's search engines to facilitate queries and return relevant information. Despite its importance, little progress has been made in CIR due to the difficulty of capturing and representing contextual information about users. Numerous CIR approaches exist today, but, to the best of our knowledge, none of them offer a similar service to the one proposed in this paper. This paper proposes an alternative framework for CIR from the World Wide Web (WWW). The framework aims to improve query results (or make search results more relevant) by constructing a contextual profile based on a user's behaviour, their preferences, and a shared knowledge base, and by using this information in the search engine framework to find and return relevant information.
Keywords: Contextual information; Contextual retrieval; Contextual model; Contextual search